Long-term outcome after external tracheal stabilization due to congenital tracheal instability - Ley, Sebastian; Loukanov, Tsvetomir; Ley-Zaporozhan, Julia; Springer, Wolfgang; Sebening, Christian; Sommerburg, Olaf; Hagl, Siegfried; Gorenflo, Matthias (The annals of thoracic surgery, 2010)
Background - Long-segment tracheobronchial malacia may cause life-threatening dysfunction of the airway system at different levels. This study presents the long-term follow-up (1992 through 2008) of patients who received surgical treatment with external tracheal stabilization in our institution. - Methods - Eleven patients fulfilled the inclusion criteria. In surviving patients who presented for reexamination, pulmonary function testing, ergometry, and magnetic resonance imaging (MRI) were performed. - Results - All patients could be weaned from the ventilator and discharged. Patients were aged a median 11 months (range, 3 to 48 months) at operation for tracheal compression. Age at follow-up was 9.1 years (range, 0.5 to 16.3 years). Median follow-up was 7.3 years (range, 0.1 to 15.1 years). Postoperatively, 1 patient was lost to follow-up, and 4 died at 2.6 years (range, 0.5 to 6.6 years) of comorbidities. Pulmonary function testing showed a moderate residual airflow restriction, with maximal vital capacity at 75% of normal (range, 45% to 92%). Treadmill exercise testing demonstrated 70% to 89% of the expected normal values for age. Magnetic resonance imaging examination confirmed tracheal patency, but the lumen of the left main bronchus in 2 patients was 50% smaller than on the right. Diaphragmatic motion was normal in all patients. - Conclusions - Children with congenital tracheal stenosis benefit from external tracheal stabilization. Survival in patients after external tracheal stabilization is significantly influenced by concomitant conditions.